Rekonstruksi Nilai Keadilan dalam Penetapan Margin Murabahah di PT. Amanah Finance Makassar - Lukman Ali (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2016)
This study aimed to (1) analyze the mechanism for setting margin murabaha PT. Amanah Finance Makassar, (2) analyzing the reconstruction value of fairness in determining margin murabaha PT. Amanah Finance Makassar. The object of research is PT. Amanah Finance Makassar. This type of research is a field research (field research). Data collection method used, namely (1) observation, (2) interviews, and (3) documentation. The data in this study is divided into two kinds of data, primary data and secondary data. Sources of primary data is archived murabahah, management and customers of PT. Amanah Finance Makassar. While secondary data sources, namely books, journals, and other sources of study other theories that it contains a discussion of the values of justice and determination of margin murabaha. Data were analyzed using descriptive method of analysis, namely an analysis of research that is intended to describe a particular factual situation systematically and accurately, which includes data reduction, data display and data verification. The results showed that the margin financing for the sale of products with murabahah PT. Amanah Finance Makassar is identical to the mark-up pricing method that is 1% -1.5% / month. PT. Amanah Finance has reconstructed the values of justice. It is based on the principle of justice: a) between the interests of customers and the BMT, b) the enforcement of Islamic economics syi'ar with the company's operational capability (including the interests of profit-seeking), and c) the ability of PT. Amanah Finance outlining the company with a significant market determination of margin proportional (not too small and not too big).Keywords: value of justice, margin of murabaha